Peningkatan Kapasitas Masyarakat melalui Pengolahan Limbah Organik untuk Pupuk Tanaman di Pekarangan Perkotaan - Siti Nurul Rofiqo Irwan; Nasih Widya Yuwono; Retno Nur Utami; Haviah Hafidhotul Ilmiah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The most sources of waste have been from households in urban area. The urban high population and daily food consumption effect the waste is potential to pollute the environment. Innovation of waste treatment should be applied by local community in urban area to reduce the household waste. This activity was a community service program UGM 2022 and supporting the Bantul Government program "Bantul free of waste 2025". The aims of this program were to improve community capacity and practice through household organic waste treatment. The activity was carried out at the Singosaren Padukuhan, Wukirsari Village, Imogiri, Bantul Regency, Special Region of Yogyakarta (DIY), in April‒October 2022. The method of program in community were included of field learning by teaching and practicing, community assistance, and evaluation of implementation. The 35 participants of PKK group from Singosaren hamlet joined this program that divided into 6 groups from 5 neighbourhood organisation (Rukun Tentangga). Organic waste process can be processed through fermentation of fresh organic waste (FLOS) or ecoenzyme and into liquid organic fertilizer using the stacked bucket (POCET) for 2–3 months. The FLOS and POCET products of waste fermentation are used as liquid fertilizers for cultivating plants in their yard Pekarangan. FLOS can also be used as multi-purpose liquid cleaner for home appliances. The raw materials included of fruit rind and vegetable waste. The results have showed the community enthusiasm, community capacity on organic waste processing and its utilization independently in the community. The application of FLOS and POCET as plant fertilizer showed better growing of plants in urban home gaden Pekarangan.